Proteomics of the red blood cell carbonylome during blood banking of erythrocyte concentrates. Issue 3 (20th January 2016) - Delobel, Julien; Prudent, Michel; Tissot, Jean‐Daniel; Lion, Niels
Abstract : Purpose: Transfusion of red blood cells (RBCs) is a daily medical procedure. Erythrocyte concentrates (ECs) can be stored up to 56 days at 4°C in saline additive solution mainly composed of adenine and sugar. Such nonphysiological conditions induce the occurrence of storage lesions, such as alterations of metabolism, protein oxidation, and deterioration of rheological properties. Their accumulation tends to decrease the main EC therapeutic property, that is, the oxygenation capacity. Protein carbonylation is a marker of oxidative stress and aging, and its occurrence during RBC storage was earlier characterized as a time‐dependent and cellular compartment dependent modification. Experimental design: Three ECs from independent donations were followed. The carbolynome was here characterized in soluble and membrane extracts ( n ‐dodecyl β‐d‐ maltoside‐based extraction buffer) of RBCs stored for 6, 27, and 41 days, through biotin hydrazide derivatization, biotin–avidin affinity purification, SDS‐PAGE separation, and LC‐MS/MS analyses. Results: A total of 142 and 20 proteins were identified as carbonylated in soluble and membrane extracts, respectively. Particularly, a time‐dependent evolution of 26.8% of the soluble carbonylome was observed. Conclusions and clinical relevance: Affected cellular mechanisms involve antioxidant defenses, metabolism pathways, and proteasomal degradation. To better store RBCs those functions have to be preserved, which opens new routes of investigation in transfusion medicine.